Inheritance Rights of Children of Extramarital in the Perspective of Balinese Customary Law After Constitutional Court Decision Number 46/PUU-VIII/2010 - MAHARANI, Trisna Sandya; SUJANA, I Nyoman; PUSPADMA, I Nyoman Alit (Journal of Political And Legal Sovereignty, 2023)
Purpose:This Article analyzes the inheritance rights of children of extramarital in the perspective of Balinese Customary Law after Constitutional Court Decision Number 46/PUU-VIII/2010. This study is focused on the children born with extramarital inheritance as regulated under the customary law in Bali after the issuance of the Constitutional Court Decision regarding children of extramarital.Methodology:This research is conducted with normative legal methods by applying the statutory, conceptual, and case approaches. The theory of justice and legal certainty is applied as the tools for analyzing legal issues as the focus of the study.Findings:After the analysis, it can be understood that the inheritance rights of children born extramarital under customary law in Bali are still marginalized because for them to obtain the position of being an heir, the Balinese customary law and community still consider legal marriage as determining point whether a person can become an heir or not.Implication: Even though the Supreme Court Decision determines that the biological father has a civil relationship with a child born extramarital, providing that it can be proven by science or technology and or for other evidence under the applicable laws and regulations or other supporting evidence legally, but if the ratification is not carried out for husband and wife relationship through a religious ceremony as referred to in Article 2 Paragraph (1) of the Marriage Law, then a child born of extramarital still has no relationship in terms of inheritance to his father's kinship lineage or patrilineal kinship lineage. Children born of extramarital have an inheritance relationship with their mother or their mother's family.